2014
DOI: 10.1063/1.4867042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of internal electric field on InAs/GaAs quantum dot solar cells

Abstract: We studied time-resolved carrier recombination in InAs/GaAs quantum dot (QD) solar cells. The electric field in a p-i-n diode structure spatially separates photoexcited carriers in QDs, strongly affecting the conversion efficiency of intermediate-band solar cells. The radiative decay lifetime is dramatically reduced in a strong electric field (193 kV/cm) by efficient recombination due to strong carrier localization in each QD and significant tunneling-assisted electron escape. Conversely, an electric field of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 27 publications
(35 reference statements)
1
38
0
Order By: Relevance
“…We consider electric fields both parallel to the growth direction [001] (labelled as E p ) and anti-parallel to the growth direction (labelled as E a ). The magnitude of the electric fields is varied between 0 and 45 KV/cm, which is in accordance with the range of the electric fields recently investigated in an experimental study for the design of solar cell devices [25]. The atomistic simulations are performed using nanoelectronic modeling tool NEMO-3D [42][43][44].…”
Section: − Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…We consider electric fields both parallel to the growth direction [001] (labelled as E p ) and anti-parallel to the growth direction (labelled as E a ). The magnitude of the electric fields is varied between 0 and 45 KV/cm, which is in accordance with the range of the electric fields recently investigated in an experimental study for the design of solar cell devices [25]. The atomistic simulations are performed using nanoelectronic modeling tool NEMO-3D [42][43][44].…”
Section: − Theoretical Frameworkmentioning
confidence: 99%
“…published experiments. The experimental studies [16,25] have not reported any In-Ga intermixing for the QDMs. Therefore we have ignored this effect in our simulations.…”
Section: − Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of the internal electric field on carrier escape and separation was investigated quantitatively by Kasamatsu et al 50 They have experimentally fabricated InAs/GaAs QDSC with different built-in electric fields by controlling the thickness of intrinsic buffer layers surrounding the InAs/GaAs QDs. The internal electric fields applied to the QDs were estimated as 46 and 193 kV∕cm when the total intrinsic layer thicknesses were 299.3 and 69.8 nm, respectively.…”
Section: Carrier Escape Nature and Electric Field Effectmentioning
confidence: 99%